If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -3x = 4x Solving -2 + -3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + -3x + -4x = 4x + -4x Combine like terms: -3x + -4x = -7x -2 + -7x = 4x + -4x Combine like terms: 4x + -4x = 0 -2 + -7x = 0 Add '2' to each side of the equation. -2 + 2 + -7x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -7x = 0 + 2 -7x = 0 + 2 Combine like terms: 0 + 2 = 2 -7x = 2 Divide each side by '-7'. x = -0.2857142857 Simplifying x = -0.2857142857
| 2x^2+mx-3=0 | | 3X-18=-4 | | 13-6(x-16)=-33 | | 5+(-4x-26)=8 | | 3x^2+4=130 | | 32x-14x=10 | | 22x+35=12x+8 | | 9-5(x-6)=-10 | | 9-3(x-2)=-10 | | (3x-1)(3x+1)=-20 | | 30+1=303129 | | 3X=0.08(3) | | -4+15=17 | | 4-3(x-2)=-10 | | 15x-14=40 | | 2x+2y=142 | | 12b+3=8 | | 4-y/3=-3 | | 1x-40=15 | | 3x+12y-10=0 | | 18+2=16106 | | 25x=6y+7 | | z^2-4z-3=0 | | 4y=9x+15 | | 3x-21=-4+14 | | 4x*-12x-45=0 | | X+43=92 | | 2/4ex^-8 | | a^3+216b^3= | | x^2-y=100 | | f(x)=7log(x+1) | | y=-2x+200 |